Mitral Valve Reconstruction: Early Results of a Modified Cooley Technique - Kumar, A. Sampath (1992)
One hundred fifty consecutive patients (71 female, 79 male) underwent mitral valve reconstruction from February of 1987 through February of 1991 for mitral regurgitation, with or without mitral stenosis. Of these patients, 134 had rheumatic mitral disease and required 1 or more procedures for correction. One hundred twenty-eight patients were age 30 or under. A posterior semicircular annuloplasty was performed, with the repair buttressed by a collar of Teflon felt; in addition, commissurotomy, papillary muscle splitting, chordal shortening, chordal and papillary fenestration, and closure of acquired clefts were performed as needed. Pre- and postoperative assessment of mitral regurgitation was carried out with the aid of echocardiography. Operative mortality was 3.3% (5 patients), and late mortality was 1.3% (2 patients). There were 3 episodes of thromboembolism at follow-up (mean time of occurrence, 16 months). (Texas Heart Institute Journal 1992;19:107-11)